2022
DOI: 10.1002/ente.202200858
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Performance of Lithium‐Ion Batteries Using a Two‐Layer, Hard Carbon‐Containing Silicon Anode for Use in High‐Energy Electrodes

Abstract: Lithium‐ion battery cells with high‐energy density and good fast charging properties are subject of current research. One approach to achieve high‐energy densities is the use of higher mass loadings. The challenges of these so called “thick” electrodes are transport limitations: lithium ions cannot reach all layers of the electrode, which results in a drop of performance. Possible concepts to overcome these limitations are the use of different active materials (silicon oxide, graphite, and hard carbon (HC)), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…Several ways of modifying the electrode architecture to increase fast-charging capability are contrary to current research. For instance, multilayer coating, blending of different active materials, and structuring of the electrode with laser ablation are being investigated and show an increase in fast-charging capabilities [5][6][7][8][9][10][11]. Several patterns for laser structuring, including hole, line, and grid patterns are investigated in the literature [8,10,12].…”
Section: Introductionmentioning
confidence: 99%
“…Several ways of modifying the electrode architecture to increase fast-charging capability are contrary to current research. For instance, multilayer coating, blending of different active materials, and structuring of the electrode with laser ablation are being investigated and show an increase in fast-charging capabilities [5][6][7][8][9][10][11]. Several patterns for laser structuring, including hole, line, and grid patterns are investigated in the literature [8,10,12].…”
Section: Introductionmentioning
confidence: 99%
“…Perforated electrodes effectively reduce concentration gradients, improving ionic transport and thus enabling better cell performance at elevated currents [39] . Similarly, multilayer coatings were suggested to enhance ion transport in the porous electrodes, providing higher power density [41–44] . Transfer of these approaches to ASSBs might be a viable pathway towards improved cell performance.…”
Section: Introductionmentioning
confidence: 99%
“…[39] Similarly, multilayer coatings were suggested to enhance ion transport in the porous electrodes, providing higher power density. [41][42][43][44] Transfer of these approaches to ASSBs might be a viable pathway towards improved cell performance.…”
Section: Introductionmentioning
confidence: 99%
“…Kremer et al [ 16 ] were able to show that low drying rates could improve the rate capability of high‐energy thick electrodes. Gottschalk et al [ 17 ] reported the improvement in the performance of LIB anodes by means of a two‐layered microstructure.…”
Section: Introductionmentioning
confidence: 99%